吉非替尼治疗EGFR基因突变状态不明的青年晚期肺腺癌疗效分析 (Zhongguo Fei Ai Za Zhi, 2014)
BACKGROUND AND OBJECTIVE: Lung cancer in young patients (less or equal to 45 years) is relatively rare. We explored the efficacy and survival of Gefitinib for young patients with unknown epidermal growth factor receptor (EGFR) gene mutation of advanced lung adenocarcinoma. METHODS: The clinical data of 55 young patients with unknown EGFR gene mutation in advanced lung adenocarcinoma referred to the Cancer Hospital & Institute, Chinese Academy of Medical Sciences from Jan 2006 through Dec 2010 were analyzed retrospectively. RESULTS: Of 55 young patients enrolled, the median age was 41 years. The objective response rate and disease control rate were 43.6% and 90.9%, respectively.. The median progression-free survival (PFS) was 9.0 months. Among the factors analyzed, brain metastasis had significant effect on PFS (P=0.017). The median overall survival (OS) was 24.0 months. The independent prognostic factors to significantly improve OS included non-smoking history (P=0.028) and receiving other anti-cancer treatment after Gefitinib therapy (P < 0.001). CONCLUSION: The median PFS and OS of the young patients with Unknown EGFR gene mutation in advanced lung adenocarcinoma were similar with general population.